Histopathological Characteristics and Incidence of Thyroid Carcinoma in a Tertiary Care Hospital of Pakistan - A retrospective study - Nazma Kiran, Bushra Adeel, Momina Khadija Abbasi, Ayesha Imtiaz Malik, Nadia Aslam, Sumera Sharif, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Thyroid cancer is the most frequently occurring cancer of endocrine organs. From the past few decades, the prevalence of thyroid carcinoma is increasing generally and this has aroused the great public concern.Papillary thyroid carcinoma is primarily responsible for this high prevalence.The cases of other types of thyroid malignancies have remained stable over time. Aim: To analyze our institution-based trends in histopathological characteristics and incidence of thyroid carcinoma. Study Design: Retrospective study Place and duration: Pathology Department of Rai Medical College, Sargodha, from July 2017 to June 2022. Methodology: This study comprised of 56 cases of thyroid neoplasm diagnosed on biopsy. The main histologic types of thyroid carcinoma include papillary, follicular, medullary and anaplastic. Results: Of 374 thyroid lesions reviewed, 56 cases were malignant. Among these, PTC constituted about 43(76.78%) cases. There were 6(10.71%) cases of follicular ca followed by 5(8.92%) cases of medullary and 1(1.78%) case of anaplastic carcinoma. Practical implication: Unfortunately, the frequency of thyroid cancer in Pakistan is on the increaseandthe incidence of thyroid cancer in our country is difficult to measure due to the limitations of epidemiological statistics. Information regarding the geographic distribution of thyroid cancer is of great value for formulating epidemiologic hypothesis and for understanding the concepts of its risk factors. Such info is also valuable for making worldwide comparisons. Conclusion: Thyroid cancer was six times more frequent in females (female-to-male ratio 6:1). Most cases of PTC, follicular carcinoma and medullary carcinoma were in patients in the fourth decade of life then in third and fifth decade. However, anaplastic carcinoma was seen between 60 to 69 years of age. Keywords: Thyroid Neoplasms, Thyroid Cancer, Papillary, Thyroid Carcinoma, Anaplastic